Structural And Functional Features Of Ovarian Formation In The Early Postnatal Period - Akramova Mahfuza Yuldashevna (Periodica Journal, 2026)
This article aims to determine the specific morphological and immunohistochemical signs of the formation of a child's ovary in the embryonic and early postpartum period in girls. Morphologically and histochemically, the ovaries of 22 infants who died from asphyxia up to 3 months were studied. The results of the study showed that in the reproductive period, the development of ovarian dysfunction caused by pathologies in embryonic ontogenesis was detected. It was confirmed that the pathologies of the embryonic period affected the development of the ovary as a dangerous factor, leading to the development of hypoxia, dishormonal interaction, dystrophy and damage to ovarian tissue, the development of the main morphofunctional structures of the ovary, can be destroyed, necrosized in the fetal period, develop reparative inflammation or lead to hyperplasia.
Keywords: infant; ovary; early postnatal period